KATEGORI SINTAKSIS ALIH KODE DI KECAMATAN PALLANGGA KABUPATEN GOWA: SOSIOLINGUISTIK INTERAKSIONAL) (Syntactic Category of Code Switching in Pallangga Subdistrict Gowa Regency: Interactional Sociolinguistic) - Hastianah Hastianah (SAWERIGADING, 2015)
The research’s purpose is to describe syntactic category of code switching in Makassarese-Indonesia language in buying and selling process of pagandeng. It is descriptive qualitative method. Data of the research is spoken and written data obtained by library and field study. Library research uses tapping participatory, recording, and noting technique. The data is analyzed based on interactional sociolinguistic. Result of analysis uncovers that syntactic category of code switching symptom in pagandeng community consists of three parts, they are:a) word order, b) word form, and c) intonation.